Preparation And Characterization Of Carbon Doped Tio2 Using Humic Acid And Its Modified Derivative As Carbon Precursors For Enhanced Photocatalytic Activities - Ismail, Ismariza (2011)
TiO2, one of the semiconductor photocatalysts with environmental friendly and economical characteristics had attracted scientific interest over the last 10 years. However, TiO2 can only be activated by UV light corresponding to its large band gap of 3.2 eV. One of the possible approaches in improving the photocatalytic activitiy of TiO2 was via doping of foreign atoms such as non-metallic elements like N, C and S. In this study, carbon doped TiO2 was prepared by using humic acid (HA) and its modified derivative, peat coagulant (PC) respectively, as the carbon precursors.